Kajian Level Realitas Terhadap Bentuk dan Elemen Arsitektural pada Rumah Vernakular: Studi Kasus Rumah Vernakular Kelurahan Jabungan Kota Semarang - Hana Faza Surya Rusyda; M Suryadi (Endogami: Jurnal Ilmiah Kajian Antropologi, 2020)
The vernacular house is a heritage building that still exists which is usually inhabited for generations. Some people in Indonesia still live in vernacular houses, one of which is in Jabungan Village, Semarang City. The forms and architectural elements that make up the vernacular house are not changed much, as if it were an artefact in the house. This can be explored more deeply about the meaning or idea of a vernacular house, it requires research based on levels of reality. The five levels of reality are empirical reality, symbolic reality, meaning reality, idea reality, and value reality/ worldview. The approach to be carried out is by studying literature and field studies by means of documentation and interviews. The conclusions obtained were in the form of a finding of the level of reality on the artefacts of a vernacular house and architectural elements that exist in Jabungan Village, Semarang City.